Image-Based Sexual Abuse as a Means of Coercive Control: Victim-Survivor Experiences - Henry, Nicola (Violence against women, 2023)
Scholars and practitioners increasingly acknowledge the ways that abusive partners create, distribute, or threaten to distribute intimate images without consent, yet little empirical research has comprehensively explored image-based sexual abuse within intimate partner contexts. This article responds to this gap and reports on the findings of a study involving interviews with 29 women and one gender-diverse person who experienced image-based sexual abuse as part of a pattern of “coercive control.” The authors argue that abusive partners use intimate imagery as a means of exerting power and control, and as a tactic of intimidation, entrapment, and degradation. They note that law, policy, and practice responses should recognize the gendered nature of image-based sexual abuse and its growing use as a means of coercive control.